Supramolecular routes to a bio-inspired synthesis of micro-and nano-structured materials - Marzec, Bartosz (Trinity College (Dublin, Ireland). School of Chemistry, 2013)
This thesis presents a contribution to the research field of coordination chemistry and synthesis of hybrid, organic-inorganic materials. The weak, non-covalent interactions that occur between the synthesised metal complexes gives rise to hierarchical supramolecular assemblies and allow the study of the self-assembly and self-organisation processes that may be used in the future bottom-up’ approaches to design intelligent materials or functional nanodevices. Fourteen new coordination compounds that contain iminodiacetic acid based ligands were characterised using a variety of analytical techniques, including single crystal X-ray diffraction in order to determine their coordination environments and solid-state packing modes. The structures and constitution of related non- crystalline materials were compared to those of the crystalline materials and were primarily characterised by electron microscopy approaches and other supplemental analytical techniques. Attention was directed to the elucidation of suramolecular packing arrangements of the molecular subunits. It was observed that hydrophobic, alkyl substituents generally promote the formation of layered, lamellar structures with clearly defined hydrophobic ‘organic’ and hydrophilic ‘inorganic’ areas. In a consecutive step the compounds were thermolysed and the morphology of the residues was investigated using electron microscopy in an attempt to establish links between the supramolecular packing structure and the morphology of the precursor material and the morphology of the residues. In several cases existence of flat, plate-like, almost two-dimensional crystals of copper(II) oxide, copper(II) oxide, calcium oxide and calcium carbonate was confirmed; these observations and layered imprints may be attributable to the initial pre-arrangement of the starting materials within 3D supramolecular networks. Furthermore the amphiphilic iminodiacetic acid-based pheniolic ligands were employed as habit modifiers for CaCO3 crystals. Chapter I introduces the reader to the subject area of supramolecular chemistry and highlights relevant compounds that contain related ligands. This chapter also summarises aspects relevant to biomimetic crystallisation of calcium carbonate. Chapter II outlines the aims of the research project. Chapter III describes coordination complexes and supramolecular packing structures containing iminodiacetic-acid based phenolic ligands, Cu(II) and Zn(II) ions. The solid-state structures are discussed along with the thermal degradation pathways and the morphologies of the residual CuO and ZnO materials. A reaction between the C2vda ligand and Cu2+ ions yielded the formation of [Cu(C2vda)(H2O)].2H2O.2MeOH (1), when TEA was used as a base, or [Cu3(µ-Cl)2(µ-C2vda)(C2vda)(H2O)4].H2O (2), when KOH was added to deprotonate the ligand. Complexation of the C6vda ligand with Cu2+ ions resulted in the generation of two new complexes: [Cu(C6vda)(H2O)2] (3), which forms in the presence of TEA, and K2[Cu2(μ-Cl)2(C6vda)2].4H2O (4) that forms in the presence of KOH. The utilisation of the C10vda ligand in a reaction with Cu2+ resulted in [Cu(C10vda)(H2O)2] (5). Compounds 1 and 2 form H-bonded layers, sandwiched between layers of constitutional solvent molecules, while compounds 3-5 display a layered lamellar packing arrangements. The final compound discussed in this chapter, [Zn(Me2hda)(H2O)2].H2O (6), forms when the Me2hda ligand is reacted with Zn2+ ions and also adopts a layered lamellar packing motif. 1-6 formed single-crystalline phases. Chapter IV contains the description of 8 new Ca-containing coordination complexes and studies on the morphology of their thermal degradation products. Calcium carbonate gained much attention in materials science as it is used as the main building material for exoskeletons of many marine organisms; it also plays a major role in the formation of hard tissues in higher organisms, including humans. The global carbon cycle depends on the abilities of sea organisms such as coral reefs or algae to capture CO2 and bind it in the form of CaCO3. It is commonly used as a model material to study biomineralisation processes. Compound [Ca2(Chnida)2(H2O)2].4H2O (7) adopts a three dimensional network structure. The utilisation of the Me2hda ligand in this reaction results in the formation of [Ca(Me2hda)(H2O)3].½H2O.½MeOH (8), while a ligand of similar amphiphilicity, C2vda, gives [Ca(C2vda)(H2O)2].H2O (9). Compounds 8 and 9 adopt layered lamellar packing motifs. Further extension of the hydrophobic part of the ligands resulted in the formation of self-assembled, non-crystalline compounds [Ca(C6vda)(H2O)2].H2O (10), [Ca(C10vda)(H2O)2] (11) and [Ca(C12hda)(H2O)2].H2O (12),. These amorphous phases were confirmed by TEM to adopt hierarchical, lamellar arrangements. The t-Bu2hda and Bc2hda ligands stabilise [Ca(t-Bu2hda)(H2O)2].3H2O (13) and K2(H2O)5[Ca(H2Bc2hda)(HBc2hda)(H2O)4]Cl.H2O (14) complexes. 13 forms an amorphous phase, while 14 is a crystalline forming a potassium-ion mediated network structure. Another research aspect presented in this thesis relates to the control over morphology of calcium carbonate crystals as described in chapter V. The aforementioned hda and vda ligands were introduced into the crystallising system in low concentration (when compared with the synthesis of supramolecular compounds) in order to disturb the crystal nuclei formation or inhibit the growth of a specific crystal face. Spherical CaCO3 assemblies with the resemblance to the naturally occurring coccospheres were obtained when the C12hda ligand was employed as habit modifier; these and other resulting morphologies of the CaCO3 crystals are different to the rhombohedral blocks that are obtained under conventional crystallisation conditions highlighting the ability of the used hda and vda complexing agents to act as habit modifiers. Chapter VI provides the conclusions based on the research results and provides directions for future work. Finally, chapter VII contains the experimental details for the synthesis of the organic ligands and the complexes along with the details of the applied analytical techniques and equipment.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin